EKSPLORASI GAYA BAHASA DAN KEPRIBADIAN PENCERAMAH DALAM ACARA-ACARA DAKWAH: STUDI KASUS DAKWAH USTADZAH HALIMAH ALAYDRUS MELALUI MEDIA YOUTUBE - Topikurrohman; Maulidia, Maya (LPPM Stikosa - AWS, 2024)
The aim of this researcher is to determine the language style and personality of the speaker at the da'wah event with a case study of Ustadzah Halimah Alaydrus' preaching via YouTube media. The computer-mediated communication (CMC) research method was used in this research, and the data source was indirect observation via Ustadzah Halimah Alaydrus' YouTube account regarding the way of delivering da'wah, language spoken, personality, background and others. Due to keeping up with the times and seeing the increasing number of social media users, research findings show that Ustadzah Halimah Alaydrus's language style and personality in her preaching via YouTube is distinctive with her gentle, straightforward and firm delivery. With the personality that Ustadzah Halimah has, she is a figure with high credibility through the education she has taken, and with special rights as a descendant of the prophet.Keywords: Language Style, Personality, Da'wah, Ustadzah Halimah Alaydrus, Youtube Media